Ultrasmall phosphorescent polymer dots for ratiometric oxygen sensing and photodynamic cancer therapy - Shi, Huifang (2014)
A series of semiconducting polymer dots (Pdots) composed of phosphorescent Ir(III) complexes and polyfluorene units in the main polymer chains are designed, synthesized, and applied in ratiometric oxygen sensing and photodynamic cancer therapy. The ultrasmall Pdots with particle size less than 10 nm are fabricated in aqueous solution on account of amphiphilic nature of the polymers. The Pdots possess fine photostability, biocompatibility, and efficient energy transfer from the polymer main chain to the Ir(III) complex. By utilizing the excited-state energy transfer from phosphorescent Pdots to the ground state molecular oxygen, these Pdots are applied in the optical sensing of oxygen with ratiometric and naked-eye detection as well as high sensitivity in aqueous solution. The Pdots also show low cytotoxicity and can pass across the cell membrane to enter into the cytoplasm. The singlet oxygen photo-generated from the Pdots under irradiation at 488 nm can effectively induce the apoptosis and death of tumor cells for photodynamic cancer therapy in vitro.